A New Wind Speed Retrieval Method for an Ocean Surface Using the Waveform Width of a Laser Altimeter. Issue 4 (4th July 2017) - Ma, Yue; Zhang, Wenhao; Li, Song; Cui, Tingwei; Li, GuoYuan; Yang, Fanlin
ABSTRACT: The current retrieval method of sea wind speeds using a space-borne laser device is based on the received energies, which are significantly influenced by the absorption and scatter effect in the atmosphere. A new method is derived to retrieve the wind speed by the path of waveform width—root mean square (RMS) surface height—wind speed, which differs from the classical path of received energy—mean sea slope—wind speed. First, by deriving a more rigorous expression of the waveform model of an ocean surface for a laser altimeter, the theoretical relationship between the surface height RMS and waveform width is established. Second, the surface height RMS is fitted to a new empirical formula that is related to the wind speed using the geoscience laser altimeter system (GLAS) waveform data and the National Centers for Environmental Prediction wind speeds. Then, the JONSWAP spectra with swell effect and the waveform simulator are used to generate sea surface profiles and echo waveforms to verify the new retrieval method. Finally, in a Pacific region by using GLAS waveform data, the retrieval results indicate that the bias was approximately 0.2 m/s, the RMSE was approximately 1.2 m/s, and the ratio of valid data exceeded 20%.